2018
DOI: 10.1002/pip.2977
|View full text |Cite
|
Sign up to set email alerts
|

Using hydrogen‐doped In2O3 films as a transparent back contact in (Ag,Cu)(In,Ga)Se2 solar cells

Abstract: This study evaluates the potential of hydrogen-doped In 2 O 3 (IOH) as a transparent back contact material in (Ag y ,Cu 1-y )(In 1-x ,Ga x )Se 2 solar cells. It is found that the presence of Na promotes the creation of Ga 2 O 3 at the back contact during (Ag y ,Cu 1-y )(In 1-x ,Ga x )Se 2 growth. An excessive Ga 2 O 3 formation results in a Ga depletion, which extends deep into the absorber layer.Consequently, the beneficial back surface field is removed and a detrimental reversed electrical field establishes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 31 publications
3
34
1
Order By: Relevance
“…Recently, we could identify IOH as a promising TBC material for chalcopyrite solar cells, establishing an ohmic back contact to the absorber and preserving high conductivity and transmission after absorber deposition at T CIGS = 550°C . It was found that a moderate Ga 2 O 3 formation, which occurred here as well, does not deteriorate the transport properties across the back contact junction significantly.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Recently, we could identify IOH as a promising TBC material for chalcopyrite solar cells, establishing an ohmic back contact to the absorber and preserving high conductivity and transmission after absorber deposition at T CIGS = 550°C . It was found that a moderate Ga 2 O 3 formation, which occurred here as well, does not deteriorate the transport properties across the back contact junction significantly.…”
Section: Introductionmentioning
confidence: 55%
“…Consequently, the (as grown amorphous) IOH films are fully crystallized before CIGS growth. It was shown earlier, that a pre‐crystallization step does not only improve the transparency of the films but might also allow for a larger Na supply from the SLG substrate during absorber deposition …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum doped zinc oxide (ZnO:Al) is a common replacement with conductivity reaching that of ITO. The chemical stability of ZnO:Al is, however, generally lower than that of In 2 O 3 [96]. ZnO is also more reactive towards oxygen than In 2 O 3 and therefore requires a more strict control of the oxygen supply during deposition [97].…”
Section: Transparent Back Contactsmentioning
confidence: 99%
“…In summary, surprisingly little research has been published on transparent back contacts for kesterite solar cells and even for the more mature chalcopyrite absorbers this area is not very much explored [96,103]. In addition to the use of different passivation layers, the question of Na supply needs to be addressed.…”
Section: Transparent Back Contactsmentioning
confidence: 99%